Pembinaan Kompetensi Spiritual Siswa SMA Keberbakatan Olahraga Negeri Aceh - Fadhlil Khaliq, Syauqi (Tadabbur: Jurnal Peradaban Islam, 2024)
The objectives of the research are, 1) to find out how to develop the spiritual competence of SMAKON students, 2) to find out what efforts are made to develop the spiritual competence of Aceh State Sports Gifted High School students. The research method used in this research is a descriptive qualitative approach. Data collection techniques were carried out by means of observation, interviews and documentation. The results of the research found that, 1) there are four methods of developing the spiritual competence of Aceh State Sports Gifted High School students, namely through the methods of habituation, example, discipline, and giving advice (mauidzah hasanah). 2) There are five efforts made by teachers in fostering the spiritual competence of Aceh State Olahara Gifted High School students, namely by increasing the teacher's spiritual pedagogical competence, requiring students to pray midday prayers in congregation, providing guidance on reading the Al-Qur’an, accustoming students to be honest, and train students to always be grateful.